2018
DOI: 10.4103/jnrp.jnrp_391_17
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Treated Primary Spinal Cord Neoplasms in Southeastern Nigeria

Abstract: Background:Primary spinal cord tumors are not as frequently encountered as their cranial counterparts. They could present in such an indolent manner that requires a reasonable index of suspicion for their diagnosis to be considered.Objective:The objective of this study is to analyze the incidence and pattern of primary spinal cord and appendage neoplasms in patients surgically treated in our institution over a decade of practice.Materials and Methods:A retrospective review of clinical, radiological, and histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
9
2
Order By: Relevance
“…-Uncommonly signal; T2WI -T2-weighted image; T1WI -T1-weighted images; MRI -Magnetic resonance imaging; FLAIR -Fluid-attenuated inversion recovery determining characteristics, indicating that a spinal lesion is an arteriovenous malformation. [1] Through a review of the literature and our experience, in Table 5, we summarized some important radiologic features of our most common spinal lesions on MRIs which can guide doctors to correct diagnosis.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…-Uncommonly signal; T2WI -T2-weighted image; T1WI -T1-weighted images; MRI -Magnetic resonance imaging; FLAIR -Fluid-attenuated inversion recovery determining characteristics, indicating that a spinal lesion is an arteriovenous malformation. [1] Through a review of the literature and our experience, in Table 5, we summarized some important radiologic features of our most common spinal lesions on MRIs which can guide doctors to correct diagnosis.…”
Section: Nomentioning
confidence: 99%
“…[3] Despite that most primary spinal cord tumors are histopathologically similar to primary intracranial tumors, spinal cord tumors are 10 times less commonly seen. [1] As the clinical presentation could be nonspecific, the patients may present with serious radicular or local pain and motor dysfunction. [4,5] Therefore, most of the patients are wrongly diagnosed with degenerative spinal disease, cervical spondylopathy, or intervertebral disk herniation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The frequency of IDEM tumours as a subset of all spinal tumours varies widely in the literature, as does the relative prevalence of the different types of tumour within this group. 2,[4][5][6] Our patients do, on average, present late. This could be due to the socio-economic challenges prevalent in the demographic of patients that access public hospitals.…”
Section: Discussionmentioning
confidence: 54%
“…In several instances, we found that the cord was sufficiently mobilised laterally even by tumours that originate ventrally, allowing laminectomy based surgery from a posterior approach. 5 Where this is not the case, however, then more anterior approaches are called into play; these include the anterior cervical corpectomy and fusion, as well as the costotransversectomy and transthoracic approaches to the thoracic spine. These approaches require a higher skill set and equipment than does a laminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Decompressive laminectomy is one of the most used approaches in the treatment of spinal tumors. Several recent studies have shown that laminoplasty is superior to decompressive laminectomy in terms of prognosis and outcomes [25,26]. Instability may occur during the surgical treatment of spinal tumors and methods requiring stabilization should be used [27][28][29].…”
Section: Discussionmentioning
confidence: 99%